تغير خصائص الهطل الفصلي والسنوي في المنطقة الساحلية من سورية خلال الفترة 1960-2010 - سكاف ميشيل; صقر رنا (Latakia University Journal -Biological Sciences Series, 2016)
تعد تغيرات نماذج الهطل أحد أهم الأخطار التي تواجه النظم البيئية الأرضية ، وموارد المياه في مختلف مناطق العالم. تم استخدام قيم الهطل الشهرية لست محطات متيورولوجية في المنطقة الساحلية من سورية ، ولفترة رصد تمتد من عام 1960 حتى عام 2010 ، من أجل دراسة التغير في خصائص الهطل في هذه المنطقة. تم استخدام خطوط الاتجاه مع اختبار مان كندال ، وكذلك توزع غاما ، إضافة إلى مؤشر تركز الهطل من أجل كشف التغير في كل من كميات الهطل للفصول ، والموسم الماطر ، وموسمية الهطل. أظهرت النتائج وجود اتجاه واضح نحو تناقص الهطل للموسم الماطر في جميع المحطات وصل إلى30% في بعضها، هذا التناقص ناتج عن تراجع كل من هطولات الربيع والشتاء ، حيث تراوحت قيمة التناقص لفصل الربيع بين 38.5 و50.2% ، ولفصل الشتاء بين 14% و38% , وعلى الرغم من التناقص الحاد في هطولات الموسم الماطر فإن موسمية الهطل عملياً لم تتغير. هذه التغيرات في نماذج الهطل سوف تشكل تحدياً كبيراً لإدارة الموارد المائية ، والانتاج الزراعي ، وإدارة الغابات. Changes in precipitation patterns are considered one of most important hazards facing terrestrial ecosystems and water resources worldwide. Monthly rainfall data for six meteorological stations located in the Syrian coastal region were used to study changes in precipitation characteristics during the period 1960-2010. Trends with mann- Kendall Test, Gamma Distribution and Precipitation Concentration Index (PCI) were applied to detect changes in seasonal and annual precipitation amount in addition to seasonality. Results showed significant negative trends in annual precipitation in all stations up to 30% in some cases, which could be related to the decrease in spring and winter rainfall amounts that ranged between 38.5% to 50.2% in spring and 14% to 38% in winter. Despite significant decrease in annual precipitation, there were no significant trends in seasonality. These changes in precipitation patterns would pose big challenges to water resources management , agricultural production and forests management.